Cara Menjaga Kesehatan Gigi dan Mulut untuk Mengatasi Kegoyangan Gigi pada Lansia - Octarina; Kusnoto, Joko; Djamil, Melanie Sadono; Nofrizal, Riko; Maitimu, Fergie Christin; Kusnadi, Stephanie Justine (Universitas Trisakti, 2024)
As people age, their overall health status, including oral health, tends to decline. Among the elderly, oral health issues often receive less attention, making proper education essential regarding common problems such as tooth mobility and ways to maintain oral health. This community service activity was conducted for the elderly in RT 014 / RW 008, Jatipulo Village, Palmerah District, West Jakarta. The method used in the counseling session included presentations and demonstrations with educational aids. Participants' knowledge was evaluated before and after the session to assess the program's effectiveness using multiple-choice questionnaires. The evaluation results showed an increase in the average post-test scores compared to the pre-test scores. Thus, it can be concluded that this counseling activity successfully improved the knowledge of the elderly in RT 014 / RW 008, Jatipulo Village, Palmerah District, West Jakarta, regarding oral health.